O031 Pelvic Inflammatory Disease (PID), Mycoplasma genitalium and macrolide resistance in England. (30th June 2016) - Dean, Gillian; Whetham, Jennifer; Soni, Suneeta; Pitt, Rachel; Alexander, Sarah
Abstract : Background/introduction: Mycoplasma genitalium (MG) is increasingly implicated in PID pathogenesis with many studies showing MG is as common as chlamydia in high-risk women. Current PID treatment guidelines specify antibiotics with low efficacy against MG. Increasing reports of macrolide resistance suggests first line treatment for MG (azithromycin) may have limitations. Aim(s)/objectives: To document rates of MG in a cohort of women with acute PID, and the proportion with baseline macrolide resistance. Methods: As part of a multicentre, open-label, non-inferiority RCT comparing ofloxacin/metronidazole (arm-1) with azithromycin 1g day-1; 500 mg od day 2–5, metronidazole/ceftriaxone (arm-2), samples were collected for baseline chlamydia, gonorrhoea and mycoplasma infection. Microbiological cure rates were documented at 6–8 weeks. Positive MG specimens were examined for macrolide resistance using a 23S rRNA PCR. Results: 313 women were recruited, median age 25. Preliminary results showed chlamydia was confirmed in 9.5%, MG in 8.2% and gonorrhoea in 0.4%. Of the 16 samples available for resistance testing, 9 (56%) had macrolide resistance mutations (A2058G/T, A2059G/C) at baseline. The reference laboratory received test-of-cure samples for only 8 patients with MG, of which 6 were negative, however 2 remained positive, both with A2059G nucleotide substitutions. Further results will be presented. Discussion/conclusion: MG infection was nearly as common as chlamydia in this cohort. Failure of patients to return at 6–8 weeks affected our ability to properly assess test-of-cure rates. Baseline macrolide resistance was unexpectedly high and impacted negatively on treatment success.